Trust management in vehicular ad hoc networks: a survey. (25th July 2019) - Souissi, Ilhem; Azzouna, Nadia Ben; Berradia, Tahar
The vehicular ad hoc networks (VANETs) provide a variety of applications that aim to ensure a safe and comfort driving experience. These applications rely on the communication and the exchange of data between vehicles. These entities are exposed to many security threats that may affect the reliability of the provided applications. Accordingly, there is a need for a trust management scheme that has to cope with the security threats and the high dynamicity of the network topology. In this paper, we survey the recent advances in trust management for VANETs. The aim of this paper is to show the importance of an adaptive trust model that can deal with the requirements of each class of applications. Therefore, we have presented well-defined criteria to point out the key issues of the existing studies and to set up some insights for research within this scope.